FAKTOR YANG MENENTUKAN KEPUTUSAN KONSUMEN DALAM PEMBELIAN TANAMAN HIAS AGLONEMA PADA USAHA MICA FLOWERS DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU PROVINSI RIAU - Rawati; Fahrial (DINAMIKA PERTANIAN, 2023)
This study aims to identify the characteristics of consumers, traders, and business profiles of Aglonema ornamental plants, factors determining consumer decisions, and marketing strategies for Aglaonema ornamental plants in the Mica Flowers business in Marpoyan Damai District, Pekanbaru City, Riau Province. A total of 20 business places were chosen and they have been managed for 20 years. The method for determining the sample in this study used the accidental sampling technique. The respondents selected were 60 respondents who bought ornamental plants at Mica Flowers. The type of data used was primary and secondary data. The analytical tools used are descriptive analysis and factor analysis. Data processing used Microsoft Excel and the SPSS program. Based on the research results it is known (1) the characteristics of consumers of ornamental plants Aglonema were mostly female as much as 83.33% with an average age of 32.35 years, with an average education of 12 years of 43.33%, with a job as a housewife as much as 36.67%, and with an average income of Rp. 3,900,000. The characteristics of the Aglaonema ornamental plant trader are female, 53 years old on average, Diploma (D3) educated level with income less than IDR 5,500,000 per month. Mica Flowers' business profile has an area of ​​900 m2, with its source of capital and with a labor of 2 people. (2) The factors determining consumer decisions in purchasing Aglonema ornamental plants at Mica Flowers are formed by 1 factor consisting of 6 variables, namely the various choices of Aglonema, Aglonema colors, ease of access to the kiosk, seller friendliness, flower arrangement, and stall cleanliness. (3) The marketing strategy for Aglonema ornamental plants is to prioritize ons that mostly determine consumer purchasing decisions, taking into account the quality of the products sold, strategic locations, good service, and providing a sense of comfort to consumers by keeping the stalls clean and flowers well arranged.